Diet‐induced obesity causes visceral, but not subcutaneous, lymph node hyperplasia via increases in specific immune cell populations. (1st August 2017) - Magnuson, A. M.; Regan, D. P.; Fouts, J. K.; Booth, A. D.; Dow, S. W.; Foster, M. T.
Abstract: Objectives: The spatial proximity of adipose depots to secondary lymph nodes allows a unique relation between the two systems. Obesity, predominately visceral adiposity, links to numerous diseases; hence, we postulate that secondary lymphatics within this region contributes to disease risk. Material and methods: Male C57BL/6 mice were fed standard CHOW (18% kcal fat) or Western diet (45% kcal fat) for 7 weeks. Visceral and subcutaneous lymph nodes and associated adipose depots they occupy were excised. Lymph node morphology and resident immune cell populations were characterized via histopathology, immunofluorescence and flow cytometry. Adipose tissue immune cell populations were also characterized. Results: Obesity caused lymph node expansion, increased viable cell number and deviations in immune cell populations. These alterations were exclusive to visceral lymph nodes. Notably, pro‐inflammatory antigen presenting cells and regulatory T cells increased in number in the visceral lymph node. Obesity, however, reduced T regulatory cells in visceral lymph nodes. The visceral adipose depot also had greater reactivity towards HFD than subcutaneous, with a greater percent of macrophages, dendritic and CD8 + T cells. Immune cell number, in both the visceral and subcutaneous, however decreased as adipose depots enlarged. Conclusion: Overall, HFD has a greater influence on visceral cavity than the subcutaneous. In the visceral lymph node, but not subcutaneous, HFD‐induced obesity decreased cell populations that suppressed immune function while increasing those that regulate/activate immune response.